Professional judgement and decision-making in adventure sports coaching: the role of interaction. Issue 13 (2nd July 2016) - Collins, Loel; Collins, Dave
ABSTRACT: This qualitative study presents the view that coaching practice places demands on the coach's adaptability and flexibility. These requirements for being adaptive and flexible are met through a careful process of professional judgement and decision-making based on context-appropriate bodies of knowledge. Adventure sports coaches were selected for study on the basis that adventure sports create a hyper-dynamic environment in which these features can be examined. Thematic analysis revealed that coaches were generally well informed and practised with respect to the technical aspects of their sporting disciplines. Less positively, however, they often relied on ad hoc contextualisation of generalised theories of coaching practice to respond to the hyper-dynamic environments encountered in adventure sports. We propose that coaching practice reflects the demands of the environment, individual learning needs of the students and the task at hand. Together, these factors outwardly resemble a constraints-led approach but, we suggest, actually reflect manipulation of these parameters from a cognitive rather than an ecological perspective. This process is facilitated by a refined judgement and decision-making process, sophisticated epistemology and an explicit interaction of coaching components.